Pengukuran ketelitian gerak meja machining center berbasis laser interferometer - Darto Darto (Jurnal Penelitian, 2003)
We tested the accuracy of the machining center table movement in the X-axis direction using laser interferometer-based measurements. The accuracy of the machining center table movements tested included accuracy in positioning, accuracy in angular motion, and accuracy in the straightness of motion. By using a laser interferometer to measure the accuracy of machining center motion, it is hoped that accurate results can be obtained and can be carried out in a relatively short time. The accuracy of the measurement technique with a laser interferometer depends on the stability of the wavelength of the laser beam. The stability is influenced by environmental factors, namely pressure, temperature, and humidity.